Exercise Prevents Enhanced Postoperative Neuroinflammation and Cognitive Decline and Rectifies the Gut Microbiome in a Rat Model of Metabolic Syndrome - Feng, Xiaomei; Uchida, Yosuke; Koch, Lauren; Britton, Steve; Hu, Jun; Lutrin, David; Maze, Mervyn (Frontiers in Immunology, 2017)
Abstract (347) Introduction: Postoperative Cognitive Decline (PCD) can affect in excess of 10% of surgical patients and can be considerably higher with risk factors including advanced age, perioperative infection, and metabolic conditions such as obesity and insulin resistance. To define underlying pathophysiologic processes we used animal models including a rat model of metabolic syndrome generated by breeding for a trait of low aerobic exercise tolerance. After 35 generations the low capacity runner (LCR) rats differ 10-fold in their aerobic exercise capacity from high capacity runner (HCR) rats. The LCR rats respond to surgical procedure with an abnormal phenotype consisting of exaggerated and persistent PCD and failure to resolve neuroinflammation. We determined whether preoperative exercise can rectify the abnormal surgical phenotype. Material and Methods: Following institutional approval of the protocol each of male LCR and male HCR rats were randomly assigned to four groups and subjected to isoflurane anesthesia and tibia fracture with internal fixation (surgery) or anesthesia alone (sham surgery) and to a preoperative exercise regimen that involved walking for 10 kilometers on a treadmill over 6 weeks (exercise) or being placed on a stationary treadmill (no exercise). Feces were collected before and after exercise for assessment of gut microbiome. Three days following surgery or sham surgery the rats were tested for ability to recall a contextual aversive stimulus in a trace fear conditioning paradigm. Thereafter some rats were euthanized and the hippocampus harvested for analysis of inflammatory mediators. At three months the remainder of the rats were tested for memory recall by the probe test in a Morris Water Maze. Results: Postoperatively, LCR rats exhibited exaggerated cognitive decline both at 3 days and at 3 months that was prevented by preoperative exercise. Similarly, LCR rats had excessive postoperative neuroinflammation that was normalized by preoperative exercise. Diversity of the gut microbiome in the LCR rats improved after exercise. Discussion: Preoperative exercise eliminated the metabolic syndrome risk for the abnormal surgical phenotype and was associated with a more diverse gut microbiome. Prehabilitation with exercise should be considered as a possible intervention to prevent exaggerated and persistent PCD in high-risk settings.